2016
DOI: 10.1111/raq.12152
|View full text |Cite
|
Sign up to set email alerts
|

Showcasing metabolomic applications in aquaculture: a review

Abstract: Aquaculture production is currently challenged to meet the growing demands for seafood protein throughout the world. To achieve this growth in an efficient, safe and sustainable manner, novel tools and applications will need to be incorporated at each step of the production line. A variety of 'omics' (e.g., transcriptomics, proteomics, metabolomics) applications have already begun to emerge in aquaculture research with extreme success. A promising new 'omics' approach is metabolomics, which aims to use metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(78 citation statements)
references
References 180 publications
0
78
0
Order By: Relevance
“…In contrast to targeted approaches, the holistic nature of metabolomics helps to investigate the complexity of a biological system responding to direct exposure to an environmental condition such as nutrition (Brennan et al . ; Sébédio ; Alfaro & Young ).…”
Section: Metabolomics: a Global View Of Metabolism Subject To Specifimentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to targeted approaches, the holistic nature of metabolomics helps to investigate the complexity of a biological system responding to direct exposure to an environmental condition such as nutrition (Brennan et al . ; Sébédio ; Alfaro & Young ).…”
Section: Metabolomics: a Global View Of Metabolism Subject To Specifimentioning
confidence: 99%
“…Metabolomics in fish research focuses on the fields of environmental impact on fish, fish health and welfare and fish nutrition (Samuelsson & Larsson ; Alfaro & Young ).…”
Section: Metabolomics: a Global View Of Metabolism Subject To Specifimentioning
confidence: 99%
See 2 more Smart Citations
“…It was further suggested that metabolomics could be useful to better understand drug–host–pathogen interactions and the outcome of drug treatments in these aquatic species. Now 10 years later, it is still believed that the potential of metabolomics research with regard to aquaculture has yet to be realised (Alfaro & Young ). Although metabolomics as a research field are still in its infancy, the use of metabolomics for aquaculture application is highly relevant (Young & Alfaro ), considering that a well‐established value chain for aquaculture products (especially abalone) is in place, with the potential to expand as the market grows, and the recent advancements in metabolomics.…”
Section: Where To From Here?mentioning
confidence: 99%